Zinc Thiolate Enables Bright Cu‐Deficient Cu‐In‐S/ZnS Quantum Dots. Issue 27 (22nd May 2019) - Hansen, Eric C.; Bertram, Sophie N.; Yoo, Jason J.; Bawendi, Moungi G.
Abstract: Copper indium sulfide (CIS) colloidal quantum dots (QDs) are a promising candidate for commercially viable QD‐based optical applications, for example as colloidal photocatalysts or in luminescent solar concentrators (LSCs). CIS QDs with good photoluminescence quantum yields (PLQYs) and tunable emission wavelength via size and composition control are previously reported. However, developing an understanding and control over the growth of electronically passivating inorganic shells would enable further improvements of the photophysical properties of CIS QDs. To improve the optical properties of CIS QDs, the focus is on the growth of inorganic shells via the popular metal‐carboxylate/alkane thiol decomposition reaction. 1) The role of Zn‐carboxylate and Zn‐thiolate on the formation of ZnS shells on Cu‐deficient CIS (CDCIS) QDs is studied, 2) this knowledge is leveraged to yield >90% PLQY CDCIS/ZnS core/shell QDs, and 3) a mechanism for ZnS shells grown from zinc‐carboxylate/alkane thiol decomposition is proposed. Abstract : Zn‐thiolate (Zn(RS)2 ) favors formation of a Zn‐In‐S alloy when used to grow a ZnS shell on Cu‐In‐S quantum dots (QDs). Utilizing Zn‐thiolate, a graded shell is grown on Cu‐In‐S QDs to realize >90% record quantum yields.